English: English - Rery, Muhammad Insanul Kamil; Lubis, Rodiah Rahmawaty; Sitepu, Bobby Ramses Erguna (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction and Objective: Ocimum sanctum extract (OSE) has been shown to have antioxidant, anti-inflammatory, and antibacterial properties which are responsible for wound healing. This study aims to analyze the effect of 5%, 10%, and 15% OSE ointment on changes in collagen density and fibroblast count in Wistar rats with partial-thickness palpebral laceration. Methods: Laboratory experimental study with randomized post-test only control group design. The subjects were 30 rats divided into 5 groups: The placebo; Gentamicin 0.3%; OSE 5%; OSE 10% and OSE 15% group. The intervention was administered 2 times/day for 4 days. On the fifth day, the palpebral tissue was obtained to make histopathological preparations and to observe the collagen density and fibroblast count. Data were analyzed using Mann-Whitney, One-Way ANOVA, Kruskal Wallis, and Tamhane test. A p-value <0.05 was assigned to the statistically significant. Results: The placebo group revealed loose collagen tissue and OSE 15% and gentamicin group revealed dense collagen tissue. The low fibroblast count was in the gentamicin and OSE 15% group and the highest fibroblast count was in the placebo group with a mean of 19.77±3.29; 22,67±0,73 and 60.9±10.66 cells, respectively. There was a significant difference (p<0.001) in the collagen density and the fibroblast count based on the treatment groups. Posthoc tests revealed differences in the collagen density level and the fibroblast count between the placebo and the whole group. Conclusion: There was a significant difference between placebo and all groups of collagen density changes and fibroblast count. There was no difference between OSE 15% and gentamicin both microscopically and statistically. Keywords: Ocimum sanctum L, Extract of Ocimum sanctum L, partial-thickness palpebral laceration, fibroblast cell count, collagen density